Sarcopenia, osteoporosis and frailty. A triad comes of age - Sánchez , Ariel; Vidal, Maritza; Vidal Neira, Luis Fernando; Messina, Osvaldo D. (Revista Médica de Rosario, 2020)
The epidemiology and the clinical characteristics of three entities that lead to dysmobility, falls and fractures (osteoporosis, sarcopenia, and frailty) are reviewed. Osteoporosis is a worldwide health problem causing bone fragility and fractures. Sarcopenia is an age-associated decline of skeletal muscle mass and function. Frailty results from the accumulation of age-related deficits in different physiological systems and is a clinical state that leads to greater risks of adverse health outcomes, such as falls, fractures, hospitalizations, loss of independence, and death. The three entities have a common denominator (aging), but they can be secondary to other diseases. There are patients presenting with all three pathologies, which should be properly identified by the treating physicians. Annals of Arthritis and Clinical Rheumatology (Aceptado para publicación)